2012
DOI: 10.5535/arm.2012.36.2.197
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Human Placental Extract on Rheumatoid Arthritis in an Animal Model

Abstract: ObjectiveTo assess the efficacy of human placental extract (HPE) in an animal model of rheumatoid arthritis (RA).MethodWe used (i) KRN C57BL/6 TCR transgenic x NOD mice (KBx/N) serum transfer arthritis and (ii) collagen-induced arthritis (CIA) mice to evaluate the effi cacy of HPE (1 ul or 100 ul, intra-peritoneal, three times per week) on RA. Incidence, severity of arthritis, and hind-paw thickness were quantifi ed. Joint destruction was analyzed using modifi ed mammographic imaging. Histopathological analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous studies have demonstrated the immune inhibitory effect of HPE in allergic dermatitis and arthritis . We hypothesize that HPE might impair the distribution of CD4+ T lymphocytes, thereby inhibiting the allergic response.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous studies have demonstrated the immune inhibitory effect of HPE in allergic dermatitis and arthritis . We hypothesize that HPE might impair the distribution of CD4+ T lymphocytes, thereby inhibiting the allergic response.…”
Section: Introductionmentioning
confidence: 85%
“…Furthermore, HPE has been used widely for the improvement of fatigue, anti‐inflammation, and anti‐aging. Despite this popularity, the efficacy and mechanism of HPE has not been sufficiently studied …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tissues were processed and 6 µm thick sections were stained in hematoxylin and eosin using the methods of Park et al (2012). Figure 4C1 and C2); this implies that the form of cell death was caused by oxidative stress which involves production of superoxide anions that can induce peroxidation of lipids and cause damage to membranes.…”
Section: Histologymentioning
confidence: 99%